Impaired Working Memory Updating for Emotional Stimuli in Depressed Patients - Zhang, Dandan; Xie, Hui; He, Zhenhong; Wei, Zhaoguo; Gu, Ruolei (Frontiers in Behavioral Neuroscience, 2018)
Although two previous studies have demonstrated that depressed individuals showed deficits in working memory (WM) updating of both negative and positive contents, the effects were confounded by shifting dysfunctions and the detailed neural mechanism associated with the failure in N-back task is not clear. Using a 2-back task, the current study examined the WM updating of positive, negative and neutral contents in depressed patients. It is found that depressed patients performed poorer than healthy controls only when updating positive material. Using event-related potential technique, the current study also investigated the neural correlates of updating deficits in depression. According to previous studies, the n-back task was divided into three sub-processes, i.e., encoding, matching and maintaining. Our ERP results showed that depressed patients had smaller occipital P1 for positive material compared to healthy controls, indicating their insensitivity to positive items on early encoding stage. Besides, depressed patients had larger frontal P2 and parietal late positive potential (LPP) than healthy controls irrespective of the valence of the words, reflecting that patients are inefficient during matching (P2) and maintaining (LPP) processes. These two mechanisms (insufficient attention to positive stimuli and low efficiency in matching and maintaining) together lead to the deficits of WM updating in depression.